Integrated parabolic nanolenses on MicroLED color pixels. (27th February 2018) - Demory, Brandon; Chung, Kunook; Katcher, Adam; Sui, Jingyang; Deng, Hui; Ku, Pei-Cheng
Abstract: A parabolic nanolens array coupled to the emission of a nanopillar micro-light emitting diode (LED) color pixel is shown to reduce the far field divergence. For a blue wavelength LED, the total emission is 95% collimated within a 0.5 numerical aperture zone, a 3.5x improvement over the same LED without a lens structure. This corresponds to a half-width at half-maximum (HWHM) line width reduction of 2.85 times. Using a resist reflow and etchback procedure, the nanolens array dimensions and parabolic shape are formed. Experimental measurement of the far field emission shows a HWHM linewidth reduction by a factor of 2x, reducing the divergence over the original LED.